The Ethics of International Bioethics Conferencing: Continuing the Conversation - Nancy S. Jecker (19342492) (2024)
Our article, “Proposed Principles for International Bioethics Conferencing: Anti-Discriminatory, Global, and Inclusive,” urged a critical conversation with bioethicists around the globe on the ethics of international bioethics conferencing (Jecker et al. Citation2024). Focusing on site selection, we tentatively set forth seven principles: anti-discriminatory, international, green, fair-minded, leave no one behind, free exchange of ideas, and epistemic justice. We appreciate the vigorous response our proposal generated, and the overall recognition of the ethical importance of the topic. We are grateful to Van Der Graaf and colleagues, who were the first in the literature to pinpoint the need for sustained debate within bioethics on the ethics of ethics conferencing (Van Der Graaf et al. Citation2023). We cannot do justice to all points colleagues raised across 15 separate commentaries. In this short response, we focus on objections and proposed addenda to the seven principles. Other Information Published in: The American Journal of Bioethics License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/15265161.2024.2316530